Leucine‐rich repeat kinase 2 regulates tau phosphorylation through direct activation of glycogen synthase kinase‐3β. (28th November 2013) - Kawakami, Fumitaka; Shimada, Naoki; Ohta, Etsuro; Kagiya, Go; Kawashima, Rei; Maekawa, Tatsunori; Maruyama, Hiroko; Ichikawa, Takafumi
<x xml:space="preserve">Abstract</x> Leucine‐rich repeat kinase 2 (LRRK2) has been identified as the causal molecule for autosomal‐dominant Parkinson's disease (PD). Experimental evidence indicates that LRRK2 may play an important role in the pathology induced by abnormal phosphorylation of tau. In the present study, we demonstrated that LRRK2 directly associates with GSK‐3β, and that this interaction enhances the kinase activity of GSK‐3β. Furthermore, we found that LRRK2‐mediated activation of GSK‐3β induces high phosphorylation of tau at Ser396 in SH‐SY5Y cells. From our present findings, we conclude that LRRK2 may function as a novel enhancer for GSK‐3β and as a physiological regulator of neurite outgrowth and axonal transport through regulation of the GSK‐3β‐mediated phosphorylation of tau at the cellular level. Since LRRK2 is detected in tau‐positive inclusions in brain tissue affected by various neurodegenerative disorders, including PD, LRRK2‐stimulated phosphorylation of tau by GSK‐3β may be involved in development of pathological features in the initial stage of PD. Structured digital abstract LRKK2 physically interacts with GSK-3B by anti bait coimmunoprecipitation (View interaction) LRRK2 physically interacts with GSK-3B by anti tag coimmunoprecipitation (View interaction) LRRK2 binds to GSK-3B by pull down (View interaction) GSK-3B physically interacts with LRRK2 and TAU by pull down (View interaction)